An open letter to The BMJ editors on qualitative research. (10th February 2016) - Greenhalgh, Trisha; Annandale, Ellen; Ashcroft, Richard; Barlow, James; Black, Nick; Bleakley, Alan; Boaden, Ruth; Braithwaite, Jeffrey; Britten, Nicky; Carnevale, Franco; Checkland, Kath; Cheek, Julianne; et al.
Abstract : Seventy six senior academics from 11 countries invite The BMJ 's editors to reconsider their policy of rejecting qualitative research on the grounds of low priority. They challenge the journal to develop a proactive, scholarly, and pluralist approach to research that aligns with its stated mission